2020
DOI: 10.1152/jn.00506.2020
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive weighting of taste and odor cues during flavor choice

Abstract: Colloquially referred to as "taste", flavor is in reality a thoroughly multisensory experience. Yet, a mechanistic understanding of the multisensory computations underlying flavor perception and food choice is lacking. Here, we used a multisensory flavor choice task in rats to test specific predictions of the statistically-optimal integration framework, which has previously yielded much insight into cue integration in other multisensory systems. Our results confirm three key predictions of this framework in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…While different researchers have come to different conclusions to this question (e.g., see the quote from Munger in Hammond, 2017 , mentioned earlier), it might anyway be argued that threshold measures are actually of rather less relevance than any spatial differences in people's responses to suprathreshold taste stimuli (see Feeney and Hayes, 2014 ; Hyde and Witherly, 1993 ). Ultimately, one of the important points to stress here is that taste localization, just like other aspects of flavour perception, is a fundamentally multisensory phenomenon ( Maier and Elliott, 2020 ; Simon et al, 2006 ; Spence et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…While different researchers have come to different conclusions to this question (e.g., see the quote from Munger in Hammond, 2017 , mentioned earlier), it might anyway be argued that threshold measures are actually of rather less relevance than any spatial differences in people's responses to suprathreshold taste stimuli (see Feeney and Hayes, 2014 ; Hyde and Witherly, 1993 ). Ultimately, one of the important points to stress here is that taste localization, just like other aspects of flavour perception, is a fundamentally multisensory phenomenon ( Maier and Elliott, 2020 ; Simon et al, 2006 ; Spence et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…), influences various aspects of taste/flavour perception is critically evaluated. We discuss various approaches to conceptualizing colour's influence over taste/flavour, including Ecological Valence Theory [86], Colour-in-Context Theory [34], the increasingly-popular Bayesian Decision Theory (see [59,70]), and suggest a network modelling approach as a potential future computational direction for the field. We briefly summarize the limited evidence concerning the neural underpinnings of colour-flavour interaction, highlight a number of the problems that are associated with trying to model colour's influence over taste/flavour perception, and offer guidance for future research.…”
Section: Outline Of Reviewmentioning
confidence: 99%
“…However, Marks and colleagues have argued that, in the case of olfaction and gustation, the noise is pooled across the flavour senses [72].) Recent work [70] has demonstrated that this approach to modelling the combination of olfactory and gustatory cues can be successfully used to predict flavour choice (i.e., preference) in rats. In humans, meanwhile, those combinations of olfactory and gustatory cues that commonly co-occur in the foods that we consume have been shown to exhibit enhanced integration, including increased 'oral referral' [66,67] (see also [140], for a review), as well as a greater crossmodal, or multisensory enhancement of smell by taste [17,27].…”
Section: Modelling Colour-flavour Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Largely, this sensory information is transmitted centrally along separate pathways, but the integration of these three intraoral senses into a unitary object generates the perception of flavor (Small, 2012 ). As a consequence, the intraoral sensations associated with eating are inherently related (Schul et al, 1996 ; Sakai and Yamamoto, 2001 ; Sakai and Imada, 2003 ; Torregrossa et al, 2012 ; Blankenship et al, 2019 ; Fredericksen et al, 2019 ; Elliott and Maier, 2020 ; Maier and Elliott, 2020 ; McQueen et al, 2020 ). Our current understanding of the behavioral and neural relationships between the intraoral senses is due in large part to many notable human studies (Arabie and Moskowitz, 1971 ; Moskowitz, 1973 ; Bartoshuk et al, 1982 ; Frank et al, 1993 ; Stevenson et al, 1995 ; Dalton et al, 2000 ; Hollowood et al, 2002 ; De Araujo et al, 2003 ; de Araujo et al, 2013 ; Prescott et al, 2004 ; Small et al, 2004 , 2008 ; Veldhuizen et al, 2010 ; Lim and Johnson, 2011 ; Veldhuizen and Small, 2011 ; Green et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%